Determinan Intensi Kepatuhan Wajib Pajak UMKM Berdasarkan Theory of Planned Behavior : Studi pada UMKM Kota Salatiga - Okta Natalia; Eni Endaryati (AKUNTANSI 45, 2026)
This study aims to analyze the influence of attitude, subjective norms, and perceived behavioral control on the tax compliance intention of MSME taxpayers in Salatiga City based on the Theory of Planned Behavior (TPB). This research adopts a quantitative approach using a survey method by distributing questionnaires to 100 MSME respondents selected through purposive sampling. The data were analyzed using SPSS, including validity tests, reliability tests, classical assumption tests, as well as multiple linear regressionl analysis, t-ltest, F-ltest, and coefficient of determination.The results indicate that attitude, subjective norms, and perceived behavioral control have a positive and significantl effect on MSME taxpayers’ compliance intention, both partially and simultaneously. Perceived behavioral control is identified as the most dominant factor influencing tax compliance intention. This study contributes to the development of the Theory of Planned Behavior in the context of MSME tax complianc,especially in Salatiga City, and provides recommendations for the Directorate General of Taxes in improving tax education strategies and enhancing MSME tax compliance.